2015
DOI: 10.1063/1.4906746
|View full text |Cite
|
Sign up to set email alerts
|

Approximating high-dimensional dynamics by barycentric coordinates with linear programming

Abstract: A novel coefficient for detecting and quantifying asymmetry of California electricity market based on asymmetric detrended cross-correlation analysis Chaos: An Interdisciplinary Journal of Nonlinear Science 26, 063109 (2016) The increasing development of novel methods and techniques facilitates the measurement of high-dimensional time series but challenges our ability for accurate modeling and predictions. The use of a general mathematical model requires the inclusion of many parameters, which are difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The development of a tailor-designed mathematical model using barycentric coordinates for high-dimensional space confirmed this notion. The method has been proven successful for a wide range of uses, from weather forecasting to creation of musical instruments with natural sounds (Hirata et al, 2015). Our studies also revealed that the intercellular coupling or circadian communication among shoot apex clocks confer robustness against genetic mutations and pharmacological perturbations.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The development of a tailor-designed mathematical model using barycentric coordinates for high-dimensional space confirmed this notion. The method has been proven successful for a wide range of uses, from weather forecasting to creation of musical instruments with natural sounds (Hirata et al, 2015). Our studies also revealed that the intercellular coupling or circadian communication among shoot apex clocks confer robustness against genetic mutations and pharmacological perturbations.…”
Section: Discussionmentioning
confidence: 71%
“…Our results indicate that intercellular communication might be important for rhythms at the shoot apex. To mathematically explore the degree of intercellular coupling, we developed a predictive model by using barycentric coordinates for high-dimensional space (Hirata et al, 2015). The model involves the use of linear programming that assigns different weights to neighboring cells and identifies the strength of coupling based on the accuracy of the predictions given the weights.…”
Section: Intercellular Circadian Coupling Among Clock Cells Of the Shoot Apexmentioning
confidence: 99%
See 1 more Smart Citation
“…We will use this method to identify the causal relation for oberved short time-series data or small samples, for which most of existing methods may fail due to insufficient information. This method is based on barycentric coordinates obtained by tessellation [ 21 ] which was extended to high-dimensional phase space that can model a high-dimensional time series [ 22 ]. We first make basic assumption for our method, i.e., the observed data of variables are from the same system or share a common attractor.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding weight w(t′) for ( ) t  in Equation 15 is optimized based on Hirata et al (2014):…”
Section: Proposed Algorithm To Forecast Unprecedented River Stagesmentioning
confidence: 99%